Learning to Cycle: A Cross-Cultural and Cross-Generational Comparison - Cordovil, Rita; Mercê, Cristiana; Branco, Marco; Lopes, Frederico; Catela, David; Hasanen, Elina; Laukkanen, Arto; Tortella, Patrizia; Fumagalli, Guido; Sá, Cristina; Jidovtseff, Boris; Zeuwts, Linus; et al. (Frontiers in Public Health, 2022)
Background Learning to cycle is an important milestone for children, but the popularity of cycling and the environmental factors that promote the development and practice of this foundational movement skill vary among cultures and across time. This present study aimed to investigate if country of residence and the generation in which a person was born influence the age at which people learn to cycle. Methods Data were collected through an online survey between November 2019 and December 2020. For this study, a total of 9,589 responses were obtained for adults (self-report) and children (parental report) living in 10 countries (Portugal, Italy, Brazil, Finland, Spain, Belgium, United Kingdom, Mexico, Croatia, and the Netherlands). Participants were grouped according to their year of birth with 20-year periods approximately corresponding to 3 generations: 1960–79 (generation X; n = 2,214); 1980–99 (generation Y; n = 3,994); 2000–2019 (generation Z; n = 3,381). Results A two-way ANOVA showed a significant effect of country, F(9,8628) = 90.17, p < 0.001, ηp2 = 0.086, and generation, F(2,8628) = 47.21, p < 0.001, ηp2 = 0.122, on the age at which individuals learn to cycle. Countries with the lowest learning age were the Netherlands, Finland and Belgium and countries with the highest learning age were Brazil and Mexico. Furthermore, the age at which one learns to cycle has decreased across generations. There was also a significant country x generation interaction effect on learning age, F(18,8628) = 2.90, p < 0.001; however, this effect was negligible (ηp2 = 0.006). Conclusions These findings support the socio-ecological perspective that learning to cycle is a process affected by both proximal and distal influences, including individual, environment and time.